A Role for Dopamine-Mediated Learning in the Pathophysiology and Treatment of Parkinson’s Disease - Jeff A. Beeler; Michael J. Frank; John McDaid; Erin Alexander; Susie Turkson; Maria Sol Bernandez; Daniel S. McGehee; Xiaoxi Zhuang (Cell Reports, 2012)
Dopamine contributes to corticostriatal plasticity and motor learning. Dopamine denervation profoundly alters motor performance, as in Parkinson’s disease (PD); however, the extent to which these symptoms reflect impaired motor learning is unknown. Here, we demonstrate a D2 receptor blockade-induced aberrant learning that impedes future motor performance when dopamine signaling is restored, an effect diminished by coadministration of adenosine antagonists during blockade. We hypothesize that an inappropriate corticostriatal potentiation in striatopallidal cells of the indirect pathway underlies aberrant learning. We demonstrate synaptic potentiation in striatopallidal neurons induced by D2 blockade and diminished by application of an adenosine antagonist, consistent with behavioral observations. A neurocomputational model of the basal ganglia recapitulates the behavioral pattern and further links aberrant learning to plasticity in the indirect pathway. Thus, D2-mediated aberrant learning may contribute to motor deficits in PD, suggesting new avenues for the development of therapeutics.